STRENGTHENING THE ROLE OF COMMUNITY IN THE MITIGATION AND ADAPTATION OF THE COVID-19 IN SOUTH KONAWE DISTRICT - Suryani Suryani; Loly Subhiaty Idrus; Ruslin Ruslin; Rini Hamsidi (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Transmission of COVID-19 developed rapidly until the World Health Organization (WHO) established a pandemic status on COVID-19 since March 11, 2020. Various of government efforts in the context of prevention and treatment have been carried out including lockdowns decisision, social distancing and new normal was currently carried out. Objective: This community service activity aims as an effort to increase the knowledge and awareness of South Konawe communities to prevent and fight covid-19 by clean and healthy living behaviors. Method: The implementation of this activity using socialization and persuasive communication online methods via social media instagram and youtube and offline method performed in two categories, small-scale and large-scale at South Konawe. These community service activities are outlined in 4 main programs, GERMAS (Healthy Living Community Movement), GEMAS (Community Movement Using Masks), socialization about TOGA (Family Medicinal Plants), antiseptics and disinfectants. Results: The result of this program is increasing public knowledges about how to improve the immune system, such as consuming nutritious food, consuming herbs which can be processed into an infusion or decocta preparations as well as understand the importance of implementing about prevention of covid-19 in daily life, such wearing masks, antiseptics, and disinfectants and washing hand correctly. Conclusion: This community service activity really helped increase the knowledge and awareness of the community of South Konawe to prevent and fight the corona virus.